Allergic and nonallergic rhinitis: Their characterization in a tropical environment - Perdomo de Ponce, Doris; Uribe, Marlene; Wolff, Ilse (Investigación Clínica, 2013)
The differences between allergic and non-allergic rhinitis were evaluated in 127 individuals from tropical urban region of Venezuela. The study design had historic data obtained regarding exacerbation of initial symptoms on exposure to common precipitants, physical examination, nasal cytology, immunodiagnostic test, routine laboratory test (fresh stool test, white cell count and urine test) and sinus x-rays. Forty nine patients were diagnosed as having allergic rhinitis (AR), 10 as probably having AR, 13 had infectious rhinitis, 4 had mixed components, 1 as non-allergic non-eosinophilic rhinitís, and 50 had no evidence of immunological nasal respiratory allergy and were taken as controlg. The associated findings with allergic rhinitis were: conjunctivitis 62%, sinusitis 23%, and bronchial asthma 24%. Our results support a significative prevalence of allergic rhinitis in this particular group, with similar symptom patterns to that of industrialized countries.